2011
DOI: 10.4028/www.scientific.net/amr.356-360.2241
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Green Cutting Process with Water Vapor for the Cooling Lubricant

Abstract: From the perspective of clean production process, this paper summarizes the present research status of green cooling machining at home and abroad and analyzes the problems of coolant cooling during machining metal materials in traditional method and. The green cutting process tests using water vapor for cooling lubricant were done and the single-factor method was used. The cutting tests for the high-temperature alloy GH4169, titanium alloy TC4 and stainless steel Cr12 were done by the carbide cutting toolsunde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The tool life extended by two-six times than dry cutting, about two-four times than oil water emulsion during machining Ti-6Al-4V with application of water vapor direct into the cutting zone. Ren et al [10] investigated the effect of saturated vapor pressure, nozzle diameter, and cooling distance on cutting force and chip thickness in the water vapor jet assisted cutting of C45 steel. The results showed that increase of saturated vapor pressure, and decrease of cooling distance and nozzle diameter caused the reduction of cutting force and chip thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The tool life extended by two-six times than dry cutting, about two-four times than oil water emulsion during machining Ti-6Al-4V with application of water vapor direct into the cutting zone. Ren et al [10] investigated the effect of saturated vapor pressure, nozzle diameter, and cooling distance on cutting force and chip thickness in the water vapor jet assisted cutting of C45 steel. The results showed that increase of saturated vapor pressure, and decrease of cooling distance and nozzle diameter caused the reduction of cutting force and chip thickness.…”
Section: Introductionmentioning
confidence: 99%